Favorable outcome of children and adolescents undergoing lung transplantation at a European adult center in the new era. Issue 11 (15th January 2016) - Schmid, Florian A.; Inci, Ilhan; Bürgi, Urs; Hillinger, Sven; Schneiter, Didier; Opitz, Isabelle; Huber, Lars C.; Isenring, Bruno D.; Jungraithmayr, Wolfgang; Schuurmans, Macé M.; Weder, Walter; Benden, Christian
Summary: Lung transplantation (LTx) is an accepted therapy in children with end‐stage lung diseases. Pediatric‐specific experience is considered important in pediatric LTx. We present our institutional experience and its outcome since the year 2000, asking whether different treatment strategies produce comparable outcomes in pediatric lung transplant recipients at our predominantly adult center. This is a retrospective analysis of children and adolescents aged ≤20 years, undergoing LTx between January 2001 and December 2013. Minimum follow‐up was 12 months. Primary endpoints were re‐transplantation or death. We performed 33 lung transplant procedures in 29 patients. Survival 1 month post‐operatively was 96.6%, at 3 months 93.1% and at 12 months 82.8%, respectively. At the end of our follow up, 72.4% of our pediatric cohort was still alive — median post‐transplant survival was 59 months (range 0–159). 72.4% of the children were transplanted with support of extracorporeal membrane oxygenation (ECMO), size‐reduced donor grafts were used in 69.0%. The differences between post‐transplant survival of the "non‐ECMO‐group" versus the "ECMO‐group" (137 vs. 28 months, P =0.7) and "full size" versus "size‐reduced bilateral transplants" (61 vs. 28 months, P  = 0.7) were not significant, though. There were no anastomotic complications, also not in size‐reduced lungs. Our results are well comparable to the international data and show excellent short‐ and mid‐term outcomes. We advocate ECMO‐bridge to be considered as a valuable treatment option to prolong time on the waiting list in highly selected patients, as well as size reduction and lobar transplants as a strong strategy to increase the donor pool and reduce donor‐recipient size‐mismatches.Pediatr Pulmonol. 2016;51:1222–1228. © 2016 Wiley Periodicals, Inc.